PENILAIAN BERBASIS KELAS BERORIENTASI HOTS BERDASARKAN TAKSONOMI BLOOM PADA PEMBELAJARAN PAI - Hasan Baharun; Kholifatus Sa’diyah (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
This paper presents a conception of class-based assessments oriented to the Higher Order Thinking Skill, based on the taxonomy of bloom to streamline the learning of Islamic Education. Class-based assessment is an activity carried out to obtain and streamline data on student learning outcomes at the classroom level, during teaching and learning activities. class-based assessments oriented to the Higher Order Thinking Skill in learning Islamic Education, is not an instant assessment and without any follow-up improvements. HOTS-oriented assessment is a continuous assessment to get feedback on subsequent learning. Through the HOTS-oriented assessment, students will be able to think creatively, critically, innovatively, argue, solve problems, and have expertise in making decisions, especially on material about Islamic Education. After the teacher performs class-based assessments oriented to the Higher Order Thinking Skills, based on the taxonomy of bloom, the teacher needs to make improvements in a directed and sustainable manner. The results of the assessment obtained, serve as reference material or reference for improvement in learning Islamic Education so on.